PENGARUH FIRM SIZE, LIKUIDITAS, DAN KEPEMILIKAN MANAJERIAL TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - IRNA TRIANNUR LUBIS; ETTY HARYA NINGSI; SELVI ARISTANTYA; IRMA HERLIZA RIZKI; MALKIT KAUR (JURNAL ILMIAH SIMANTEK, 2020)
The purpose of this study was to determine the effect of Firm Size, Liquidity, Managerial Ownership, on the Dividend Payout Ratio in Banking Companies Listed on the Indonesia Stock Exchange (IDX) for the 2013-2017 period. The research method used is quantitative. Data collection technique is to use secondary data. The sample in this study was 155, using purposive sampling technique. This study uses multiple linear regression analysis which first tested the classical assumption with normality test, multicollinearity test and heteroscedasticity test. Hypothesis test is done by F test, t test and determination test. The results show that Firm Size, Liquidity, Managerial Ownership, have a joint effect on the Dividend Payout Ratio. Firm Size has a significant effect on the Dividend Payout Ratio. Liquidity has a significant effect on the Dividend Payout Ratio. Managerial Ownership has no effect on the Dividend Payout Ratio in Banking Companies Listed on the Indonesia Stock Exchange (IDX) for the 2013-2017 period.